Adherence to diet with higher dietary diabetes risk reduction score is associated with reduced risk of type 2 diabetes incident in Iranian adults - Mitra Kazemi Jahromi; Hossein Farhadnejad; Farshad Teymoori; Golaleh Asghari; Mahsa Kalantari; Parvin Mirmiran; Fereidoun Azizi (BMC, 2023)
Abstract Background The Dietary diabetes risk reduction score (DDRRS) has recently been considered by researchers as a diet quality index to predict the risk of chronic diseases, such as type 2 diabetes (T2D). In this study, we aimed to assess the association of DDRRS with T2D risk in Iranian adults. Methods Subjects aged ≥ 40 years without T2D (n = 2081) were selected for the current study from participants of the Tehran Lipid and Glucose Study (2009-2011) and followed for a mean of 6.01 years. We used the food frequency questionnaire to determine the DDRRS that is characterized by eight components, including higher consumption of nuts, cereal fiber, coffee, and polyunsaturated to saturated fat ratio and lower consumption of red or processed meats, trans fats, sugar-sweetened beverages, and high glycemic index foods. The multivariable logistic regression analysis was used to determine the odds ratio (ORs) and 95% confidence interval (CI) of T2D across the DDRRS tertiles. Results The mean ± SD age of individuals was 50.4 ± 8.2 years at baseline. The Median (25-75 interquartile range) DDRRS of the study population was 24(22-27). During the study follow-up, 233(11.2%) new cases of T2D were ascertained. In the age and sex-adjusted model, the odds of T2D were decreased across tertiles of DDRRS (OR = 0.68; 95%CI: 0.48-0.97, P for trend = 0.037). Based on the multivariable-adjusted model, after controlling all potential confounders, the risk of T2D is reduced across tertiles of DDRRS (OR = 0.66; 95%CI: 0.44-0.98, P for trend = 0.047). Also, higher scores (lower consumption) of red and processed meat (OR = 0.59; 95%CI: 0.39-0.88, P = 0.012) and sugar-sweetened beverages (OR = 0.49; 95%CI: 0.32-0.76, P = 0.002) as DDRRS components were associated with decreased T2D incident. Conclusions Our findings suggested that a diet with a higher score of DDRRS may be related to reducing the risk of T2D in Iranian adults.